Teddy bear,teddy bear, open your eyes - Krutop, Lee (Brimax Publishing Victoria, Australia, 2007)
This children's rhyme, "Teddy Bear, Teddy Bear," is a classic that encourages interaction and engagement. It invites young children to participate in the story by mimicking the actions described in the rhyme, such as opening their eyes. The repetition and simple language make it easy for children to learn and enjoy.